Stability of discrete non-conservative systems - Lerbet, Jean, 1961-; Challamel, Noel; Nicot, Francois; Darve, F. (Discrete granular mechanics set., 2020)
Stability of Discrete Non-conservative Systems first exposes the general concepts and results concerning stability issues. It then presents an approach of stability that is different from Lyapunov which leads to the second order work criterion. Thanks to the new concept of Kinematic Structural Stability, a complete equivalence between two approaches of stability is obtained for a divergent type of stability. Extensions to flutter instability, to continuous systems, and to the dual questions concerning the measure of non-conservativeness provides a full, fresh look at these fundamental questions. A special chapter is devoted to applications for granular systems.